2021
DOI: 10.31101/juara.v4i1.1494
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework of Built Environment Factors on Cycling Behaviour among Residential Neighbourhoods

Abstract: Cycling as one of a mode of transport in urban and residential areas has been determined as a solution for the urban issue. It is an active and environmentally friendly mode of travel. However, the relationship between the physical built environment cyclingbehaviour among residential are less associated with increasing the bike-ability of residents. The main factors as a major contributor to bike-ability behaviour are built environment and social factors. The main aspect to determine the interaction between al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(14 reference statements)
0
1
1
Order By: Relevance
“…The results obtained are analogous to those of Rivera-Navarro et al [49], who found that residents were more physically active in the presence of various sports facilities in the neighborhood than in the absence of sports facilities in the neighborhood. The results are different from the studies of Bogdanovic and Mitkovic [39] and Haron et al [50], which suggest that the creation of pedestrian paths and bicycle paths promotes physical activity, yet the studies did not establish a link between the provision of pedestrian paths and bicycle paths to commuting that included physical activity.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The results obtained are analogous to those of Rivera-Navarro et al [49], who found that residents were more physically active in the presence of various sports facilities in the neighborhood than in the absence of sports facilities in the neighborhood. The results are different from the studies of Bogdanovic and Mitkovic [39] and Haron et al [50], which suggest that the creation of pedestrian paths and bicycle paths promotes physical activity, yet the studies did not establish a link between the provision of pedestrian paths and bicycle paths to commuting that included physical activity.…”
Section: Discussioncontrasting
confidence: 93%
“…Physical activity is linked to psychological health. Haron, Zainol, Wan Omar, and Rahman [50] examined the relationship between the provision of a cycling path and the willingness to use it in a neighborhood and found that the main factors that influenced cycling in a neighborhood were the opportunities created for cycling by the provision of paths, the benefits gained in terms of shorter paths, faster access to facilities, and the physical activity generated.…”
Section: Literature Reviewmentioning
confidence: 99%